The Polemic of Isra' Mi'raj in the Perspective of Mu'tazilite and Sunni Tafsir: A Comparative Study of Al-Kasshaf and Al-Kabir - Misbakhul Arifin; Musyarrofah Musyarrofah; Abd. Kholid (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2024)
This study examines the Isra' Mi'raj, the miraculous nocturnal journey of the Prophet Muhammad, through the lens of the tafsir interpretations of Al-Zamakhshari and Al-Razi, with a focus on the differing views of these two prominent scholars. The event, which encompasses the Prophet's journey from the Al-Haram Mosque to the Al-Aqsa Mosque and his ascension to Sidaratul Muta, where he directly encountered Allah SWT, has been subject to diverse theological and interpretative discussions. This article employs a descriptive and qualitative methodology, utilizing library research for data collection and content analysis to examine the relevant tafsīr texts. The comparative analysis reveals that Al-Zamakhshari asserts the event took place at the Al-Haram Mosque in a spiritual form, prior to the Prophet's prophethood, whereas Al-Razi posits that the Isra' Mi'raj occurred in the general Haram area, specifically in the house of Umm Hani bint Abi Talib, a year before the Hijrah, and involved both body and spirit. The study further explores the interpretive approaches of both mufassirun, highlighting differences in their methods, theological beliefs, the location of departure, the timing of the event, and the nature of the ascension itself. These findings contribute to a deeper understanding of the variances in the interpretations of this pivotal event in Islamic tradition.